Kurikulum Meja Makan - Ramses Simanjuntak (Sekolah Tinggi Theologia Nazarene Indonesia, 2020)
The dining table is a place that is made to serve food. At the dining table, you will usually be served a meal according to the desired recipe. At the dining table it is clear how family members enjoy the warmth of love, because through eating together at the dinner table all family members can tell each other stories, laugh and reminisce. The tradition and culture in Indonesia about eating with family at the dinner table has been proof of how valuable the tradition is. Through that tradition we see that Indonesian children have grown into generations of mutual respect, mutually cooperate and accept each other. For this reason, it is deemed necessary to preserve this tradition so that in the future Indonesia will give birth to generations of people who are strong and have noble character and have strong faith in the course of their lives. Eating together at the dinner table turned out to be used as an effective and creative way to instill faith in every child in the family. Parents must present qualified religious education as an instrument to introduce every child to his Savior.